Peningkatan Kompetensi Digital Marketing Program Kewirausahaan Batik Poetra Dolokgede di Kabupaten Bojonegoro Melalui Kegiatan “Sinau Bareng” Ademos Indonesia - Jokhanan Kristiyono; Dian Eka Safitri; Agis Savira N U; Trivenadyah Nurmala; Kartika Cahya Jauhariya; Hilda Kurniawati P (Prapanca : Jurnal Abdimas, 2023)
The problem of poverty and population development is still a crucial social issue in Bojonegoro district during technological development issue. As a non-governmental organization, Ademos Indonesia contributes together with local actors of small-medium enterprises (SME) in Indonesia called UMKM in developing their potential. Through research-based community service activities with the theme "Optimizing Regional Potential (Local Values) through Community Development Collaboration in the Digital Communication Era to create Character, Reliable, and Quality Students devotion." These activities based on the research aim to assist the publication process of SME's actors in Bojonegoro Regency, under Ademos Indonesia's guidance. This digital marketing concept is beneficial for SME actors to market their business through online networks. Both about expanding products, content campaigns, digital branding, and also increasing product sales. This activity in several achievements in the form of a digital branding concept of SME's Instagram media fostered, namely Batik Poetra Dolokgede. Overall, activities run smoothly and according to the timeline of the work program that has been scheduled